2019
DOI: 10.1292/jvms.19-0401
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Juzen-taiho-to against vincristine-induced toxicity in dogs

Abstract: Vincristine, one of the anti-cancer drugs used in veterinary practice, has adverse hematological and gastrointestinal effects in dogs. Juzen-taiho-to is a traditional Chinese medicine used for patients with anorexia in human medicine. However, the protective effects of Juzen-taiho-to against anti-cancer drug-induced toxicity in dogs have not been investigated. We therefore examined whether the administration of Juzen-taiho-to to dogs affects gastric motility, and vincristine-induced gastrointestinal and hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…An experimental study reported that Juzen-taiho-to ameliorated the carboplatin-induced decrease in food intake and BW in mice [16]. In our previous study, the administration of granulated Juzen-taiho-to to dogs promoted gastric contraction and reduced vincristine-induced gastrointestinal adverse reactions [14].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…An experimental study reported that Juzen-taiho-to ameliorated the carboplatin-induced decrease in food intake and BW in mice [16]. In our previous study, the administration of granulated Juzen-taiho-to to dogs promoted gastric contraction and reduced vincristine-induced gastrointestinal adverse reactions [14].…”
Section: Discussionmentioning
confidence: 85%
“…Juzen-taiho-to was reported to reduce the hematological side effects of anti-cancer drugs in mice [16]. In our previous study, Juzen-taiho-to stimulated gastric contraction and had protective effects against vincristine-induced gastrointestinal toxicity in dogs when administered at 450 mg/kg/day [14]. Considering these reports, Juzen-taiho-to may be useful in veterinary medicine to reduce the side effects of anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation